Pengaruh Menyusui Dini dan Mobilisasi Dini terhadap Tinggi Fundus Uteri Ibu Post Sectio Caesarea di Ruang Amarylis SMC RS Telogorejo (Inovasi Kesehatan Global, 2026)
A decrease in the height of the uterine fundus is an important indicator of a normal uterine involution process after childbirth. Delayed reduction of fundal height may lead to uterine subinvolution, which increases the risk of postpartum hemorrhage, particularly in post–cesarean section mothers. Early breastfeeding and early mobilization are recommended interventions to support uterine contraction, prevent vaginal bleeding, and accelerate uterine involution. This study aimed to examine the effect of early breastfeeding and early mobilization on reducing the height of the uterine fundus in post–sectio caesarea mothers treated in the Amaryllis SMC Room at Telogorejo Hospital. The study employed a quasi-experimental design with a one-group pretest–posttest approach. The population consisted of 523 post–cesarean section mothers hospitalized at SMC Telogorejo Hospital between January and November 2023. Data were collected using structured observation sheets to measure fundal height before and after the interventions. The results showed that the average uterine fundal height before early breastfeeding and early mobilization was 19.74 cm above the symphysis, while after the interventions it decreased to an average of 12.49 cm above the symphysis. Statistical analysis indicated a significant effect of early breastfeeding and early mobilization on the reduction of uterine fundal height (p = 0.000). These findings highlight the importance of implementing early breastfeeding and mobilization as part of postpartum nursing care to support uterine involution and reduce the risk of complications in post–cesarean section mothers.